THE INFLUENCE OF PARENTS' WORK ON THE DEVELOPMENT OF PERSONALITY AND CHARACTER OF CHILDREN AGED 5-6 YEARS - Andi Fausia Syam; Andi Rezeky Amaliah; Anhar Irawan; Herman Herman (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2022)
Early childhood is the right time to provide stimulus and stimulation to children as a foundation in creating and shaping children's personality and character. Character and personality can be influenced by various factors, one of which is the type of parental work. This study used a sample of 30 children aged 5-6 years who had parents with civil servant jobs, private employees and fishermen. The research approach is quantitative using Multivariate Analysis of Variance with the help of SPSS. The purpose of the study was to find out how parents' work affects the development of children's personality and character. The data collection method uses observation and distribution of questionnaires to parents using instruments based on PERMENDIKBUD No. 137 of 2014. Based on the results of research and analysis, it was found that the achievement of personality in the research sample was in the low category with a percentage of 43.33% and in the high category with a percentage of 56.67%. While in the achievement of children's character development with a low percentage of 40% and a high percentage of 60%. Overall, the research results show that based on the type of work of parents, it has an influence on the development of personality and character of children.